Komunikasi Instruksional Guru Terhadap Siswa Berkebutuhan Khusus di Sekolah Inklusif - Eka Yuli Astuti (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
This research aims to determine how the form of instructional communication that occurs between teachers and students with special needs in inclusive schools. . In conducting instructional communication, teachers need to consider the characteristics of students with special needs to be able to determine the appropriate form of communication so that learning objectives can be achieved. This study uses a qualitative approach with a descriptive method. The study was conducted in four elementary schools in Bandung City. The results of the study indicate that (1) several factors influence the form of teacher instructional communication to students with special needs which include factors of teacher competence, student characteristics, class participation, school environment readiness, and parental support; (2) in carrying out instructional communication the teacher uses various methods. channels in the form of simple and focused verbal, persuasive verbal, appropriate intonation and volume; (3) the use of multi-sensory methods that use props, clear and straighforward auditory information and visual strategies with attractive pictures.